Dynamic of blueberry buds dormancy in a region of low chill occurrence - Neiva de Carvalho, Ruy Inacio; Biasi, Luiz Antonio (Comunicata Scientiae, 2021)
Several cultivars of blueberry were introduced in the colder regions in Brazil, but presented varied vegetative and reproductive growth, due to the heterogeneity of adaptation to the regional climate. The objective of this research was to determine the dormancy dynamics of blueberry buds grown in a region of low chill occurrence. Four methods of bud dormancy evaluation were used: biological test of single node cuttings, dormancy index, tetrazolium test and Tabuenca test. The dormancy of floral and vegetative buds of the cultivars Bluebelle, Climax, Delite and Powderblue of the Rabbiteye group was studied in collections every two weeks from April 26 to July 21. In the evaluated period there were only 76 h of temperatures below 7.2° C. The biological test and the dormancy index were viable methods for the dynamic evaluation of buds dormancy. The tetrazolium test was efficient to predict the exit of the endodormancy of floral and vegetative buds, but the Tabuenca test was efficient to predict the exit of floral buds dormancy only for the cultivars of less intense dormancy. The cultivars Bluebelle and Powderblue presented better adaptation to the conditions of low cold occurrence, with well defined installation and overcoming of the dormancy. The cv. Delite is more susceptible to budding heterogeneity and the cv. Climax is the least indicated to the region.